Não mais temas o calor do sol: a morte de si e a morte do outro em Mrs. Dalloway - Selner, Raquel (2021)
Attitudes toward death differ according to time and space. The First World War, which ended in 1918, had an impact on those attitudes in populations of the whole world, mainly in the countries involved in the conflict. Virginia Woolf's novel Mrs. Dalloway, published in 1925, brings in its protagonists, Clarissa Dalloway and Septimus Warren Smith, samples of the attitudes toward death present in the English society of their time. The research aims to understand how the attitudes toward the death of oneself and of the other are represented in that novel, taking into account the socio-historical context in which it was produced. First, a bibliographic review is brought up regarding the socio-historical context in which the novel is situated, punctuating aspects regarding the current attitudes toward death at that time; then, the novel is analyzed based on its protagonists, verifying their reflections and attitudes regarding the death of themselves and of other people and their consonance with the context of the novel's production. It is noticed that the protagonists present similar views about death, but different attitudes. At the end of the novel, both unite the death of themselves and the death of the others in different ways, Septimus through suicide and Clarissa through a new beginning.